A efetividade do direito à duração razoável do processo e a responsabilização civil do estado pelo ato judicial administrativo - Vasconcelos, Fernanda Sousa (2016)
Based on the applicability of the efficiency duty to Judiciary, we seek through this work give effectiveness to the fundamental right to reasonable length of process by identifying the time as a criteria for evaluating the quality of the judicial public service provided. Is identified as a directly applicable rights or as a right that requires regulation, the State has the duty-power to achieve it, using the administrative function, legislative and even judicial to do so under the consequence of making a inefficient Constitution. Due to the hybrid nature of this right, it is necessary to assess the state responsibility for this inefficiency in its positive scope, analyzing the existence of a right to compensation for damage caused by the poor condition of the judicial public service. Because it is an indeterminate legal concept, the identification of reasonable time in each process should be clarified by filing criteria, either by the State legislator or even, in the case of omission of that, the State judge. The methodology used in this paper uses the bibliographic and documentary research, with jurisprudential analysis on the subject, which is approached in the light of constitutional law with implications in administrative and procedural levels. The existence of condemnation of Brazil by the International Court, while national courts apply the theory of irresponsibility for acts of judicial management, it demonstrates the importance of this subject, because it questions the role of the Judiciary in the enforcement of fundamental rights.